Non-specific electrocardiographic ST-T abnormalities predict mortality in patients on peritoneal dialysis - Zhan, Xiaojiang; Zeng, Chuanfei; He, Jiajing; Wang, Menghui; Xiao, Jun (Frontiers in Cardiovascular Medicine, 2022)
Background: This study aimed to evaluate the predictive value of non-specific ST-segment and/or T-wave abnormalities in electrocardiography (ECG) for all-cause and cardiovascular mortality (CVM) in peritoneal dialysis (PD) patients. Methods: All patients who started PD between November 1, 2005, and February 28, 2017, at the First Affiliated Hospital of Nanchang University were enrolled. The primary outcomes were all-cause mortality and CVM. The Kaplan–Meier method and a log-rank test were used for the survival analysis. Multivariate Cox proportional hazards models were used to investigate the risk factors for all-cause mortality and CVM. Results: A total of 724 eligible PD patients were enrolled, including 401 (55.4%) men. In total, 153 (21.1%) patients died during a mean follow-up period of 27 (interquartile range, 13–41) months, and cardiovascular death was responsible for 84 of these deaths. The patients with non-specific ST-T abnormalities had lower overall and cardiovascular survival rates compared to those free from any ECG abnormalities. According to the multivariate Cox proportional hazards models, non-specific ST-T abnormalities are independent risk factors for all-cause mortality and CVM, the hazard ratios are 1.81 (95% confidence interval, 1.11–2.95; p = 0.017) and 2.86 (95% confidence interval, 1.52–5.37; p = 0.001), respectively. Conclusions: Non-specific ST-T abnormalities can serve as risk markers of all-cause and CVM in PD patients.